Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The Readiness of the Laboratories of the College of Science at the Northern Border University to Activate the use of Virtual Laboratories from the point of view of Faculty Members Mrs. Tarfa Hamdi Khalif Alanazi , Prof. Ajlan Mohammed H. Alshehri 2. The suitability of applying the competencies system in the Public Authority for Applied Education Proposed study (case study of civil engineering departments) Eng. Ahmed Gohar Naseeb 3. The Effect of social media on Values System Among Intermediate School Female Students in Tabuk from their Parents’ Point of View (Tik Tok as a model) Mrs. Bashayer Dhafr Al-Qahtani 4. The educational values included in the book “Refining morals and purifying races” by Ibn Miskawayh (analytical study) Mrs. Samar Abdullah Alhejilan, Mrs. Nurah Saad Alharbi, Mrs. Hawadi Saleh Alsaykhan 5. The role of the educational supervisor in improving the teaching performance of Islamic studies teachers to raise the academic achievement of middle school students Mrs. Hanan Ali Al-Shehri 6. Psychometric characteristics of the deductive thinking test in the light of the paragraph response theory for high school female students in Makkah Al-Mukarramah Mrs. Faizah Ahmed M. Basakran 7. Body image and its relationship to self-esteem among pregnant women in the light of some demographic variables Mrs. Atheer Ali Alshehri